Deternation of Rapril in Pharmaceutical Dosage Forms by Reversed-Phase Liquid Chromatography - Prasada Rao, K.V.S.; Vijaya Kumari, K.; Bhanu Prakash, I.; Prabhakar, G.; Begum, Jameelunnisa (Asian Journal of Chemistry, 2010)
A rapid and sensitive HPLC method was developed for the estimation of rapril in pharmaceutical dosage forms. Rapril was chromatographed on a reverse phase C18 column, mobile phase consisting of 0.05 M KH2PO4, acetonitrile and methanol in the ratio of 40 : 40 : 20. The mobile phase was pumped at a flow rate of 1.0 mL/n and the eluent was monitored at 216 nm. The calibration curve was linear in the range of 0.5–50 μg/mL. The results of the study show that the present HPLC method is simple, precise, specific, less time consung and accurate for the estimation of rapril in pharmaceutical dosage forms.